Biblical and Classical Myths: The Mythological Framework of Western Culture - Frye, Estate of Northrop (Frye Studies, 2004)
By complementing the biblical tradition with the classical, this volume imparts a comprehensive understanding of western mythology. With a preface by Alvin Lee, general editor of the Collected Works of Northrop Frye, Biblical and Classical Myths is an essential volume and represents a unique achievement in scholarship